CO2 and steam gasification reactions of a charcoal from holm-oak wood. KINETIC AND TEXTURAL CHARACTERIZATION - Valenzuela Calahorro, C; Bernalte García, M J; Serrano Gómez, V; Bernalte García, A (BIOMASS FOR ENERGY AND INDUSTRY: 5th E.C. Conference, 1990)
In this work are shown the kinetic results of carbon dioxide and steam gasification reactions of a charcoal from holm-oak wood and the evolution of some textural parameters (BET surface area, micropore and mesopore volume) of several activated carbons prepared by such reactions
APS
Keywords: activated carbon; Carbon dioxide; charcoal; Holm oak; kinetic; steam gasification